Effect of Ethical Leadership of Company’s CSR on Employee CSR Engagement in the Era of Digital Industry Revolution - Mohd Isa, Salmi; Kong Loke, Cheng (KnE Social Sciences, 2019)
In this paper, we examined how companies are using ethical leadership CSR to interact with their employees about corporate social responsibility (CSR) related matters. A structured questionnaire was designed to elicit employees responses. Data were collected from the 200 respondents but only 154 were found usable for the data analysis. The responses were analysed using the PLS-SEM statistical technique using Smart-PLS software towards testing the proposed model. The research findings found that employee’s understanding of the company’s CSR to be the most significant predictor of employee CSR engagement accompanied by using ethical leadership with the moderating impact of Person-Organisation Fit. It is evident that social exchange values may affect employees towards Corporate Social Responsibility (CSR) engagement. Contribution to ethical leadership and CSR engagement are discussed.